Inclusive investment in the sustainable development of the agricultural sector and rural areas of Ukraine - Степаненко, С. В.; Подсоха, А. С.; Крюкова, І. О.; Халін, С. В. (Collection of papers new economy, 2023)
This scientific study is devoted to solving the tasks of overcoming these negative trends at the expense of substantiating the mechanism of inclusive investment. The article examines the essence and role of the inclusive investment mechanism in agricultural business. Based on the system of fundamental indicators, an assessment of the current level of sustainable development of the agricultural sector of Ukraine was carried out. The main trends accompanying the agrarian sector’s transition to sustainable development principles have been identified. The main directions of investment in the rural business of Ukraine have been revealed. An analysis of the sources, volumes, and dynamics of agricultural investment in solving the problems of sustainable development of agribusiness and rural areas was carried out. A prospective assessment of the amount of inclusive investment resources in the agricultural sector and the rural regions is given. The main problematic aspects related to the process of inclusive investment in Ukrainian agrarian business are characterized. The critical organizational and economic principles of forming a sustainable business model for developing an agricultural industry based on inclusive investment are substantiated. The conducted studies confirmed the presence of transformational changes in the economy of the agricultural sector of Ukraine in the direction of achieving the goals and objectives of sustainable development. The research results formed the basis for substantiating practical proposals and recommendations for improving the process of attracting inclusive investments in agricultural business and the development of rural areas.
Web of Science
Keywords: investments; agrarian business; inclusive gaps; economic and social development; performance